The patient representation struggle during the COVID‐19 pandemic: Missed opportunities for resilient healthcare systems - Hester van deBovenkamp; Bert deGraaff; Karin Kalthoff; Roland Bal (Health Expectations)
Abstract Background The role of patient participation and representation during crises, such as the COVID‐19 pandemic, has been under‐researched. Existing studies paint a pessimistic picture of patient representation during the pandemic. However, there are indications that patient representatives have adapted to the new situation and can contribute to the resilience of healthcare systems. This paper aims to further explore the potential contribution of patient representatives for healthcare system resilience during the COVID‐19 pandemic. Methods The study used a qualitative approach. We conducted a thematic analysis on the following data: interviews with client council members (n = 32) and representatives from patient organizations (n = 6) and focus groups (n = 2) to investigate patient representation on both the national policy level and organizational level in the Netherlands. Results We identified the crisis discourse, the dependent position, the diversity of patient perspectives and the layered decision‐making structure as themes that help to understand what made patient representation in pandemic times a struggle for national and local patient representatives. The analysis of the subjects these representatives put forward during decision‐making shows that their input can play an important role in broadening discussions, challenging decisions, and suggesting alternatives during a crisis. We identified several strategies (e.g., collaborating with other actors, proactively putting subjects on the policy agenda, finding new ways of contacting their ‘constituency’) used by the patient representatives studied to exert influence despite the difficulties encountered. Conclusions The struggle for patient representation during pandemic decision‐making is a missed opportunity for resilient healthcare systems as these representatives can play a role in opening up discussions and putting different perspectives to the fore. Moreover, the adaptive strategies used by representatives to influence decision‐making offer lessons for future representation activities. However, adaptations to the crisis decision‐making structure are also needed to enable patient representatives to play their role. Patient Contribution We conducted interviews with patient representatives and discussed our preliminary findings with patient representatives during the focus groups. Zorgbelang, a patient organization supporting client councils and enabling and organizing patient participation for organizations and municipalities, was partner in this research and contributed to the interview guide, conducting interviews and focus groups. Additionally, the analysis made by the first author was discussed and refined multiple times with the partners of Zorgbelang and one of them co‐authored this paper.